WEWENANG DAN TUGAS KEPOLISIAN DALAM PENANGANAN UNJUK RASA DI WILAYAH HUKUM POLRESTA YOGYAKARTA - Cahyo Suprobo; Muhammad Hatta; Eko nurharyanto (Kajian Hasil Penelitian Hukum, 2018)
This study aims to analyze and empirically search the information about the exercise of the police officer’s duties and authorities in handling a mass rally in the jurisdiction of the Yogyakarta City Police Department. It also aims to know the obstacles faced by the police officers in handling a mass rally in the jurisdiction of the Yogyakarta City Police Department. This study is normative research that reviews legal norms related to the object of the research. This study was conducted in the jurisdiction of the Yogyakarta City Police Department. This study employed secondary data which is a primary legal material in the form of legislation and the primary data from the result of the interview with the interviewee as the support for the primary legal material. The data were gathered by conducting literature study and field research. The data were analyzed qualitatively. Based on the result of the research, it can be concluded that the intensity of the event of mass rallies in the jurisdiction of the Yogyakarta City Police Department is high. The mass rally was done 172 times in 2015, 146 times in 2016, and 152 times in 2017. The actions taken by the police officers of Yogyakarta City Police Department in exercising the duties and authorities in handling the mass rally consists of 3 steps including preemptive step being initiative to precede the mass rally by persuading and communicating to reduce conflict, preventive step (preventing the anarchism in the mass rally and keeping the mass rally save, conducive, and well controlled, and repressive step some steps are taken to secure the mass rally through service and security procedures of expressing an opinion in public or a mass rally. There are two factors of the obstacles faced by the police officers in handling a mass rally in the jurisdiction of the Yogyakarta City Police Department. The first is the internal factors which are influenced by the lack of Republic of Indonesia Police personnel in Yogyakarta City Police Department Satsabhara, the different intellectuality and knowledge level of Yogyakarta City Police Department members and psychological condition and the ability to control the emotion of each member of Police Department. The second is the external factors which are influenced by the lack of coordination with the Police Department, the field condition and setting of the mass action in doing the rally, the lack of legal knowledge of the mass and the image of a police officer which is always bad in the eye of protesters.